The rich and the pure: philanthropy and the making of Christian society in early Byzantium - Caner, Daniel (The transformation of the classical heritage, 2021)
Prologue : what is a Christian gift? -- Introduction : philanthropy and asceticism in the first affluent Christian society -- A present-giving world -- Give to all who ask of you : the challenge of early Byzantine philanthropy -- Bend your heart to mercy : giving alms in early Byzantine communities -- With your whole soul : from alms to charity in early Byzantine monasticism -- What God has put in your heart : divine patronage and material blessings -- First fruits of the world : fruitbearings, penance and prosperity in the countryside -- Imperishable remembrance : offerings and the rise of patronal monasteries -- Epilogue : when holy men walked the earth.